ANALISIS DIVERSIFIKASl PRODUK KAYU OLAH.AN PADA INDUSTRI PENGGERGAJIAN TERPADU DI CEPU, JAWA TENGAH - Sylviani Sylviani (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Pro4ucta diventfication ia a mutegic tlecmon for integrated fore« indratry a it will contribute added value either in terms of income 1eneriltion or creation of employment, and to improve raw materiala. utilization and to b n rmrket opportunitin.7b He the impact of product diversification a dudy waa conducted at an integrated teak aawmill in Cepu, Central •.liva. TM •average annual UH of lo1• are 21,896.16 cum oonmting of l 9,!69.46 cum (99'£) f0r •wmDl and•J,117.80 cum• (10%) for verae-r milL TM avmwe produetioR of •wn timber ia 9,681.48 cum per year ooverift6of the espo quality grade (COS), domedic quality grade and raw materialafor further proce• with volume• 1,190 •.03 cum (74%); 1,317.80 cum (14